N Nilai-Nilai Pendidikan Agama Hindu Dalam Tradisi Pesangkepan Tilem Di Desa Batukaang Kecamatan Kintamani Kabupaten Bangli - Wayan Saniarta (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The tradition of Pesangkepan Tilem in Batukaang Village, Kintamani District, Bangli Regency is in the form of a traditional meeting at tilem which is only attended by male residents who are already married. The phenomenon that occurs in the religious life of the Batukaang Village community is that people do not understand much about the nature of the philosophical meanings and values ​​contained in it. This study examines three main problems, namely: 1) the form of implementing the Tilem Pesangkepan Tradition in Batukaang Village, Kintamani District, Bangli Regency, 2) the function of implementing the Tilem Pesangkepan Tradition in Batukaang Village, Kintamani District, Bangli Regency, 3) Hindu religious education values contained in the implementation of the Tilem Pesangkepan Tradition in Batukaang Village, Kintamani District, Bangli Regency. The theories used in this research are: 1) Religious Theory to analyze the form of implementation of the Pesangkepan Tilem Tradition, 2) Structural Functionalism Theory to analyze the function of the implementation of the Pesangkepan Tilem Tradition, 3) Value Theory to examine the values ​​of Hindu religious education contained in the implementation The tradition of Pesangkepan Tilem. Informants were selected using the snowball technique. Data was collected by observation, structured interviews, documentation, and literature study. The data analysis technique is carried out through the process of reduction, presentation, and conclusion drawing, and the final stage is the presentation of research results. The results of the research obtained from the implementation of the Pesangkepan Tilem Tradition can be seen in four aspects, namely: 1) the background of the implementation. The Pesangkepan Tilem tradition is a form of religious activity which is an embodiment of the sense of devotion of the Hindu community in Batukaang Village who has been given safety in everyday life, 2) The time of the implementation of the Tilem Pesangkepan Tradition is carried out during the Tilem (Dead Moon). The Pesangkepan Tilem tradition is held once a month, 3) The facilities used include Pesiangan Sticky Rice and Canang Ceeng. The functions of the implementation of the Pesangkepan Tilem Tradition for the Hindu community in Batukaang Village include: 1) religious functions, 2) social functions. The values ​​of Hindu religious education contained in the implementation of the Tilem Pesangkepan Tradition, namely: 1) the value of tattwa education, 2) the value of moral education, 3) the value of event education. Keywords: Pesangkepan Tilem Tradition, Religious Education